The Role of Brand Trust in Mediation of Brand Experience and Brand Image on Brand Loyalty (Case Study on XL Card Users in Malang City) - Shafaratin Nurul Hasanah; Siti Asiyah; Dwiyani Sudaryanti (Budapest International Research and Critics University, 2022)
This study aims to analyze the role of brand trust in mediating brand experience and brand image on brand loyalty . The population of this research is XL card users in Malang City. In this study, the sampling technique used non-probability sampling so that 130 respondents were determined. The data analysis method is descriptive quantitative. Quantitative analysis was performed using SmartPLS. In this study, the results showed that brand experience and brand image had a significant effect on brand trust, brand trust had an effect on brand loyalty, brand experience had an effect on brand loyalty, while brand image had no effect on brand loyalty. Brand trust is able to mediate the effect of brand experience and brand image on brand loyalty